Antibacterial activity of ovary extract from sea urchin Diadema setosum - Marimuthu, K.; Gunaselvam, P.; M. Aminur, Rahman; Xavier, R.; Arockiaraj, J.; Subramanian, S.; Md. Yusoff, Fatimah; Arshad, Aziz (Verduci Editore, 2015)
Objective: Sea urchin gonad is considered as a highly prized delicacy in several countries. It is also rich in valuable bioactive compounds including polyunsaturated fatty acids (PUFAs) and β-carotene. This study was undertaken to examine the antimicrobial properties of the ovary extract from sea urchin Diadema setosum against selected Gram-negative and Gram-positive bacteria.